Sistematización de experiencias investigativas en el pregrado de la Facultad de Odontología de la Universidad de Antioquia - Otálvaro-C., Gabriel Jaime; Orozco-A., Steven; Echeverri-V., Juan David; Rua-G., Mauricio; Marulanda-L., Heberth Alexander; Jaramillo-D., Gonzalo (Revista Facultad de Odontología Universidad de Antioquia, 2015)
Systematization is a process of the construction of knowledge parting from what the practice teaches and contributes to the improvement of material and cognitive conditions under which the analyzed experience takes place. A participative systematization of the research process of four groups contained in beginners research group was carried out. The study was a descriptive and interpretative research beginning from recovery guides, semi-structural and free conversations applied to four interest groups. Five categories were conformed for the gathering and interpretation of the information: motivation and interest, significant learning, directive process, coherence-curricular articulation, and evaluation- projections. The mandatory courses and the grouping for common thematic interests stood out as the primary interests of the process; significant learning was mediated by the role of the teacher, the dynamics that he/she gave to the group, the generated extracurricular spaces and the interaction with other areas of the institution. The results allowed them to gain an occupational and academic profile, to consolidate extracurricular experiences, to secure inter institutional, academic and professional relationships. The undergraduate level should begin as an option for the formative research that will allow the students sensitization and bring him/her closer to the methodological way of thinking, the production of disciplinary knowledge and also to understand the social phenomena that are located in a very dynamic and complex surroundings. Looked at it in this way, the beginners research groups become a fundamental tool that will empower the articulation of research in the academic, scientific, and social environment of the university.